Hunting practices and harvest of peccaries in the northern Paraguayan Dry Chaco. (April 2021) - Saldivar-Bellassai, Silvia; Feldpausch-Parker, Andrea; Giordano, Anthony J.; Frair, Jacqueline
Abstract: Overexploitation is a frequently cited driver of species extinction. Throughout the Neotropics, balancing traditional practices and the needs of local people with protection of rare or declining species is challenging, especially given low capacity for control by authorities. We conducted interviews with wildlife professionals and residents, along with a camera-based field survey of wildlife occurrence, to gain insight into recent population trends, relative abundance, and drivers of harvest for large mammals in the northern Dry Chaco of Paraguay including but not limited to, Defensores del Chaco National Park. Although the endangered Chacoan peccary ( Catagonus wagneri ) was preferred regardless of hunter motivation, harvests of all species appeared largely opportunistic, and limited to immediate family use due to a lack of market forces, and constraints on refrigeration capacity in the region. This pattern may soon change given rapid deforestation, and an associated and growing road network providing greater access both to wildlife resources and commercial bushmeat markets. Notably, public perception of abundance and trends for Chacoan peccary differed from professional opinions—likely due in part to greater use of areas along roads by C. wagneri compared to other, relatively more abundant species. This discordance may pose future challenges if harvest restrictions become a conservation necessity, especially during a process of essentially self-imposed voluntary limitations. Highlights: Motivations and factors for harvest of large mammals in the northern Paraguayan Dry Chaco ecoregion were documented. Public opinion of trend and status for the endangered Chacoan peccary differed from professional opinion. Harvests remained opportunistic due to limitations in access, but that may change given growth in road networks. Wildlife populations and harvest levels monitoring is needed given that area has some of the highest deforestation rates in the world.